Non-Financial Reporting – Examples of Good Practices in Poland - Magdalena WÓJCIK-JURKIEWICZ; Beata SADOWSKA (Communications of International Proceedings, 2020)
The article attempts to assess the current state of non-financial reporting, or rather the practices applied by companies fulfilling the statutory obligation in the first two years. The main aim of the article is to examine the current practices in Poland in the field of non-financial reporting and to attempt to evaluate them. Taking the above into account, the Authors decided that the purpose of the article is to answer two research questions: 1) Based on what good practices, companies prepare their non-financial reports, taking into account various industries? 2) What are the trends of non-financial reporting in Poland in the analysed years? A total of 94 companies were examined. The results obtained indicate that the form of disclosures made is very different. The research used research methods and techniques, including: methods of induction and deduction, analysis and synthesis, critical analysis of domestic and foreign literature on the subject, the method of comparative analysis and content analysis. Previous studies in this field did not cover the 2017 and 2018 reporting period, i.e. the first two years after the change of guidelines. Therefore, the obtained results allow to determine the level of preparation of the analysed companies, belonging to various sectors, to new reporting obligations and indicate the current trends in the field of applied practices. The authors clearly indicated, as a result of the conducted research, the need to introduce a uniform framework for the disclosure of non-financial information.
Keywords: Non-financial reporting; standards; good practices in Poland; EU Non-Financial Reporting Directive (NFRD).